#### Answer

$7$

#### Work Step by Step

The general formula for the average rate of change from $x$ to $y$ can be written as: $\dfrac{f(y)-f(x)}{y-x}$. As $y\rightarrow x$, the rate of change becomes instantaneous (derivative).
Here, we have: $f(x)=2x^2+3x+2$
$\lim\limits_{x\to 1}\dfrac{f(x)-f(1)}{x-1}=\lim\limits_{x\to 1}\dfrac{(2x^2+3x+2)-[(2)(1)^2+(3)(1)+2]]}{x-1} \\=\lim\limits_{x\to 1}\dfrac{2x^2+3x-5}{x-1} \\=\lim\limits_{x\to 1} \dfrac{(x-1)(2x+5)}{x-1} \\=\lim\limits_{x\to 1} (2x+5) \\=(2)(1)+5 \\=7$